Revision and phylogeny of the genus Andocaeculus (Acari: Caeculidae) I: the A. weyrauchi species group - Porta, Andrés O.; Pizarro-Araya, Jaime; Ramírez, Martín J. (Zootaxa, 2021)
Two new caeculid mite species, Andocaeculus beatrizrosso sp. nov. and Andocaeculus burmeisteri sp. nov., are described and A. weyrauchi (Franz, 1964) is redescribed based on material collected at the type locality. All post-larval stages are described for A. weyrauchi and Andocaeculus beatrizrosso sp. nov. and stochastic variation in the idiosomal and appendages chaetotaxy is considered. A clade of Andocaeculus containing the three species (the A. weyrauchi group) is established based on morphological characters, and confirmed with a Bayesian phylogenetic analysis of sequences from the CO1 marker. As result of the same analysis, the absence of the (st) pair of setae on leg II is proposed as a derived condition for the genus Andocaeculus, and the presence of the φ solenidion on leg IV is a derived condition for some Andocaeculus species of the A. weyrauchi species group.